Synthesis and immunological properties of Vi and di-O-acetyl pectin protein conjugates with adipic acid dihydrazide as the linker. - Kossaczka, Z (1997)
The Vi capsular polysaccharide of Salmonella typhi, a licensed vaccine for typhoid fever in individuals > or = 5 years old, induces low and short-lived antibodies in children, and reinjection does not elicit booster responses at any age. Its immunogenicity was improved by binding Vi to proteins by using N-succinimidyl-3-(2-pyridyldithio)propionate (SPDP) as a linker. Similar findings were observed with the structurally related, di-O-acetyl derivative of pectin [poly-alpha(1-->4)-D-GalpA] designated OAcP. Protein conjugates of Vi and OAcP were synthesized by carbodiimide-mediated synthesis with adipic acid dihydrazide (ADH) as the linker. Hydrazide groups were introduced into proteins (bovine serum albumin or recombinant Pseudomonas aeruginosa exoprotein A) by treatment with ADH and 1-ethyl-3(3-dimethylaminopropyl carbodiimide (EDC). The resultant adipic acid hydrazide derivatives (AH-proteins), containing 2.3 to 3.4% AH, had antigenic and physicochemical properties similar to those of the native proteins. The AH-proteins were bound to Vi and OAcP by treatment with EDC. The immunogenicity of Vi or OAcP, alone or as protein conjugates, was evaluated in young outbred mice and guinea pigs by subcutaneous injection of 2.5 and 5.0 microg, respectively, of polysaccharide, and antibodies were measured by enzyme-linked immunosorbent assay. All conjugates were significantly more immunogenic than Vi or OAcP alone and induced booster responses with 5- to 25-fold increases of antibodies. Vi conjugates were significantly more immunogenic than their OAcP analogs. A carboxymethyl derivative of yeast beta-glucan enhanced the anti-Vi response elicited by an OAcP conjugate but had no effect on the immunogenicity of Vi or of OAcP alone. Vi and OAcP conjugates synthesized by this scheme will be evaluated clinically.